Implementation of effective communication technologies and programmes for vibrant Agriculture - BHARTI, V. K.; BHAN, SURAJ; ., MEETALI; ., DEEPSHIKHA (Journal of Soil and Water Conservation, 2021)
The India is an agrarian country with a lot of natural and geographical diversities. Even in the age of industrialization, two-third of our population depends on agriculture directly or indirectly for their livelihood. Agriculture and farmers are still the backbone of our economy and strengthening their position is the ultimate objective of all the schemes and plans of our government. In any developing country, agriculture as the contributing factor of economic development is well recognized if it is realized with the help of science and technology. Series of schemes and plans for the development of agriculture and welfare of the farmers have started. Soil information has become increasingly important for many disciplines to address the conflicting pressure on limited land resources. In addition to farming community, civil engineers and agricultural engineers, environmentalists, urban planners, disaster managers and policy makers also need soil information. Though a wide range of information on soils are available in scattered and unorganized format, the modern day information system of any natural resources requires its location in terms of time and space and exact referencing or geo-referencing of important spots has become very necessary. Geographic information system has been an important tool for geo-referencing soil information system. Therefore such an organized information system would not only store the datasets for posterity but will also improve our understanding of biophysical processes in terms of relationship among them in the soil environment. Information is power in today’s world and the government has realized the need to empower the farmers with relevant information. A dedicated Kisan TV will provide information to farmer to know the price, weather and related information and help them to take timely decisions for better productivity of their crops.